Examples of the Application of Sulfur Isotopes to Economic Geology - Eric S. Cheney (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1975)
Sulfur isotopes are best used in conjunction with other geological studies to determine the origin of known deposits; concept-oriented exploration programs can then be developed to find similar deposits. Geochemical processes are capable of causing different S '41S" ratios in the minerals and fluids participating in natural reactions. Because the magnitude of the resultant isotopic difference is inversely proportional to temperature, sulfur isotopic studies can be used to determine the source of the sulfur in high temperature deposits. The narrow spread of sulfur isotopic values from ores related to cupolas of felsic intrusions suggests that the sulfur in the ore-forming fluids was derived from a fairly uniform source (such as the intrusions) rather than by heated ground water from the adjacent country rocks. However, geologic and isotopic evidence suggest that the sulfur of many nickel sulfide ores may have been derived from the country rocks rather than the associated mafic igneous rocks. This sulfurization hypothesis implies that mafic intrusions in sulfur-rich country rocks should be prime exploration targets. Sulfur isotopic analyses of sulfides in the mafic rocks may indicate whether sulfurization has occurred. In equilibrium geochemical reactions S" is concentrated in the minerals with the greater bonding strengths. Thus the isotopic compositions of coprecipitated sulfides that have not undergone exsolution may be used as geothermometers and to distinguish multiple periods of mineralization, post-ore metamorphism, etc. The sulfur isotopic compositions of coexisting sulfides at Butte, Mont., indicate that the copper minerals did not originate by simple replacement of pyrite. Geologic and isotopic evidence suggest that the mineralogical and isotopic zoning at Butte formed almost isothermally during the geochemical evolution of the ore-forming fluids upward and outward from the Central zone. Unidirectional reactions cause enrichment of S" in the products. At low temperatures the isotopic effects of bacterial and inorganic reactions are difficult to distinguish. Anaerobic sulfate-reducing bacteria apparently were responsible for the sulfur of Gulf Coast salt domes and for diagenetic pyrite in sandstone-type uranium deposits. Sulfur (and carbon) isotopic data suggest that the roll ore bodies of sandstone-type uranium deposits originated by limited inorganic oxidation of diagenetic pyrite rather than by bacterial activity. Accordingly roll ore bodies should be most numerous and thickest against those portions of the sandstone aquifer that contain pre-ore pyrite.